(untitled) (Global Journal of Science Frontier Research, 2015)
In this paper, a generalized class of exponential chain ratio-cum-chain product type estimator has been developed for estimating finite population mean and its properties have been studied in presence of non-response. The expressions for the bias and mean square error of the proposed estimator have been obtained in two different cases of non-response. The theoretical and empirical studies have been given to demonstrate the efficiency of the proposed estimator with respect to the other relevant estimators under consideration.